Quality of Life of Elderly Residing at Old Age Homes of Biratnagar Metropolitan City - Khadgi, Deepika (Tribhuvan University Journal, 2021)
Elderly is the vulnerable age; and their health status and well-being is an important area of concern which is reflected by Quality of Life (QOL). With the increasing population of the aged in developed as well as developing world, proportion of elderly living in old age homes is also in increasing trend due to migration of children and nuclear family concept. The objective of the study waste assesses the QOL of the elderly people residing in old age homes at Biratnagar with the use of WHOQOL-BREF questionnaire. Cross-sectional descriptive study including the census of the elderly living at selected old age homes was used. Data was collected from the 57 elderly meeting the inclusion criteria through face to face interview by using interview guide. The findings of the study showed that the participants were of age group from 60 and above, and 66.70%of them were female. Among 57 respondents, 42 (76.39%) were married and 15(23.61%) were unmarried. Of those married, nearly half of them (47.61%) had no children. More than 1/3 rd (71.92%) of the respondents were illiterate and nearly half (45.61%) of them were involved in agriculture in the past. As perceived by the elderly themselves, the overall quality of life was found to be good in less than half (42.10%) and overall quality of health score was found to be satisfied in more than half (59.64%) of them. Also, the study has revealed higher score in physical domain and psychological domain which reflects that the components of these domains as physical needs, health needs, religious and spiritual needs, financial needs have been addressed. Thus, it can be concluded that quality of life is perceived good by less than half and quality of health is perceived satisfactory by more than half with higher score in physical and psychological domain. However, they are in need of social support and relationship which can be promoted to some extent by inculcating the content of geriatric care in school curriculum. Also, there should be provision of visit to geriatric centers so that awareness regarding this area could be raised.